(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This thesis is about combining process mining and learning analytics approaches to reduce crowding in practice task check-feedback-retake flows. Additionally, process discovery and compliance checking are performed based on event logs collected from LMS, autograder, Git/CI, and other sources, with errors typed through clustering and sequential analysis.